Wayuu people’s views on human rights’ indivisibility (2025)
The objective of this study was to examine the perception of human rights among the indigenous Wayuu population in Colombia. This study is based on previous research conducted with Venezuelans, French, and Mozambican nationals, which suggests that human rights are generally perceived as interdependent and indivisible. The sample consisted of 95 members of the Wayuu indigenous community, aged 18 and above. The applied instrument was based on a factorial experimental design that incorporated a series of fictitious human rights scenarios from specific countries. These scenarios were constructed to combine four factors: (a) privacy, (b) equality, (c) civil liberties, and (d) social protection. The results indicate that for the majority of the Wayuu indigenous population, human rights form a whole that cannot be conveniently divided into separate parts. However, for a minority, the only factor considered is social protection. These results are consistent with those of previous research on the subject and with the socioeconomic reality of indigenous communities.